2019
DOI: 10.1080/01559982.2019.1589907
|View full text |Cite
|
Sign up to set email alerts
|

The internal accountability dynamic of UK service clubs: towards (more) intelligent accountability?

Abstract: This paper explores the nature of internal accountability within service organisations. The study adopts a cross-sectional approach, with the three largest service organisations in the world selected along with Round Table International, a popular service organisation in the UK. This paper utilises Roberts' framework of individualising/hierarchical and socialising/intelligent forms of accountability, with socialising forms of accountability dominating accountable space within service clubs. The presence of a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 58 publications
(125 reference statements)
1
29
1
Order By: Relevance
“…Through an analysis of the discussions taking place in the NGOs' online community of practice, this study reveals that the accountability agenda and related practices of advocacy NGOs is determined by the interrelated threats of financial vulnerability, potential loss of independence, legitimacy challenges and the high level of public scrutiny. Yates et al (2019), Uddin and Belal (2019) and Goncharenko (2019) support our prior assumption that within NGOs there is a greater commitment to genuinely address the interests of a broad range of stakeholders (O'Dwyer & Unerman, 2007, p. 2008) with a focus on substantive as opposed to procedural accountability (Gray et al, 2006). In these papers, the authors identified a sense of obligation towards the NGOs' purpose, rather than anxiety regarding the power of the stakeholders or financially-driven motives (O'Dwyer & Unerman, 2008).…”
Section: Ngos Social Purpose Accounting and Accountabilitymentioning
confidence: 84%
See 4 more Smart Citations
“…Through an analysis of the discussions taking place in the NGOs' online community of practice, this study reveals that the accountability agenda and related practices of advocacy NGOs is determined by the interrelated threats of financial vulnerability, potential loss of independence, legitimacy challenges and the high level of public scrutiny. Yates et al (2019), Uddin and Belal (2019) and Goncharenko (2019) support our prior assumption that within NGOs there is a greater commitment to genuinely address the interests of a broad range of stakeholders (O'Dwyer & Unerman, 2007, p. 2008) with a focus on substantive as opposed to procedural accountability (Gray et al, 2006). In these papers, the authors identified a sense of obligation towards the NGOs' purpose, rather than anxiety regarding the power of the stakeholders or financially-driven motives (O'Dwyer & Unerman, 2008).…”
Section: Ngos Social Purpose Accounting and Accountabilitymentioning
confidence: 84%
“…While most NGOs are small, the largest NGOs dominate the funding and activities within the sector (Cordery et al, 2017). Accordingly, much research focuses on the largest of these entities (as do Uddin & Belal, 2019), yet in this issue we also include research on smaller, less well-resourced entities (Denedo et al, 2019;Goncharenko, 2019;Kemp & Morgan, 2019;Yates et al, 2019). Thirdly, NGOs' work is affected by the context in which they operate.…”
Section: Ngossome Definitional Issuesmentioning
confidence: 99%
See 3 more Smart Citations